2021
DOI: 10.1038/s41387-020-00144-x
|View full text |Cite
|
Sign up to set email alerts
|

Exercise intensity regulates cytokine and klotho responses in men

Abstract: Background Short-term exercise training programs that consist of moderate intensity endurance training or high intensity interval training have become popular choices for healthy lifestyle modifications, with as little as two weeks of training being shown to improve cardiorespiratory fitness and whole-body glucose metabolism. An emerging concept in exercise biology is that exercise stimulates the release of cytokines and other factors into the blood that contribute to the beneficial effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 49 publications
1
48
0
Order By: Relevance
“…The appetite-related hormone leptin is a well-known adipokine (11,12) reported to stimulate hepcidin production in mice and cultured cells (13,14). Exercise training modulates leptin levels and sensitivity, as well as appetite (15)(16)(17), and leptininduced modulation of hepcidin may affect energy availability. Leptin is lower in body fat during fasting and acute exercise, which generally depicts the state of endurance runners (18).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The appetite-related hormone leptin is a well-known adipokine (11,12) reported to stimulate hepcidin production in mice and cultured cells (13,14). Exercise training modulates leptin levels and sensitivity, as well as appetite (15)(16)(17), and leptininduced modulation of hepcidin may affect energy availability. Leptin is lower in body fat during fasting and acute exercise, which generally depicts the state of endurance runners (18).…”
Section: Introductionmentioning
confidence: 99%
“…The type of exercise performed by athletes differentially exercise time, body fat, and hormone secretion, including leptin (15)(16)(17). In track and field clubs, endurance runners and sprinters typically engage in different types of exercise.…”
Section: Introductionmentioning
confidence: 99%
“…[25] Middelbeek et alcompared moderate-intensity endurance training and high-intensity interval training in sedentary men. [29] Exercise training reduced IL-6 concentrations in healthy men by 49% in sprint interval training and by 11% in moderate-intensity training. [29] Rose et al found that sprint and endurance training groups the levels of IL 6 and TNF-α were similar in both groups, while IL-10 levels were higher in sprinters.…”
Section: Discussionmentioning
confidence: 95%
“…[29] Exercise training reduced IL-6 concentrations in healthy men by 49% in sprint interval training and by 11% in moderate-intensity training. [29] Rose et al found that sprint and endurance training groups the levels of IL 6 and TNF-α were similar in both groups, while IL-10 levels were higher in sprinters. [30] IL-17 is a cytokine which aids T-cells in the inflammatory response.…”
Section: Discussionmentioning
confidence: 95%
“…Finally, non-invasive and non-pharmacological approaches have been reported to increase klotho. A recent study showed blood klotho concentrations were increased after 2 weeks of moderate intensity training in men [ 82 ] and even after a single bout of high-intensity exercise [ 83 , 84 ]. The effect of diet on the expression of klotho has also been investigated.…”
Section: Approaches To Increase Klotho Levels In the Brainmentioning
confidence: 99%